Spontaneous coronary dissection and asymptomatic splenic artery aneurysms in a young woman - Chyrchel, Michał; Dziewierz, Artur; Chyrchel, Bernadeta; Gallina, Tomasz; Szafrański, Oskar; Surdacki, Andrzej (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2020)
Acute coronary syndromes (ACS) remain one of the most frequent reasons for patient admissions to emergency care units. The majority of ACS are represented by myocardial infarction caused by atherosclerotic plaque rupture. Spontaneous coronary artery dissection (SCAD) remains a rare but frequently underdiagnosed cause of ACS.